Survey on Threat management system (International Journal of Engineering and Computer Science, 2017)
With the rapid change and development in the sector of Information Technology and in Network technologies; the value of data and information is also increased. Today lot of valuable data is generated using many computers based application and stored back to the company database. But unfortunately, the threat to the same data is also increasing rapidly. So, development of a proper Intrusion Detection System which provides a right alarm is a hot topic today. There are many areas which helps to build such devices and software applications like Data mining techniques, network protocol system, decision tree, clustering, SNORT, Genetic Algorithm etc. This paper presents a technique of applying evolutionary algorithm i.e. Genetic Algorithm to Intrusion Detection System. It also provides a brief and how to implement it in real IDS.